2020
DOI: 10.1371/journal.pone.0228709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pennisetum giganteum z.x.lin mixed nitrogen-fixing bacterial fertilizer on the growth, quality, soil fertility and bacterial community of pakchoi (Brassica chinensis L.)

Abstract: Biofertilizer plays a significant role in crop cultivation that had reduced its inorganic fertilizer use. The effects of inorganic fertilizer reduction combined with Pennisetum giganteum z.x. lin mixed nitrogen-fixing biofertilizer on the growth, quality, soil nutrients and diversity of the soil bacterial community in the rhizosphere soil of pakchoi were studied. The experiment composed of 6 treatments, including CK (no fertilization), DL (10% inorganic fertilizer reduction combined with Pennisetum giganteum z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Pennisetum giganteum (Pennisetum giganteum Z. X. Lin), a fast-growing and high-yield perennial C 4 grass, belongs to the genus Pennisetum in the Poaceae family. It is widely planted in over 80 countries in tropical, subtropical and temperate regions (Jia et al, 2020;Li et al, 2020). P. giganteum has high nutritional value and good palatability and has been developed as a source of forage.…”
Section: Introductionmentioning
confidence: 99%
“…Pennisetum giganteum (Pennisetum giganteum Z. X. Lin), a fast-growing and high-yield perennial C 4 grass, belongs to the genus Pennisetum in the Poaceae family. It is widely planted in over 80 countries in tropical, subtropical and temperate regions (Jia et al, 2020;Li et al, 2020). P. giganteum has high nutritional value and good palatability and has been developed as a source of forage.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that application of biofertilizers can effectively reduce the use of chemical fertilizers and pesticides. Jia et al (2020) found that biofertilizers can replace 25% of chemical fertilizers without a detectable impact on the yield and quality of Chinese cabbage. Other studies have shown that inoculation with T. harzianum strains significantly increased the biomass and nutrient uptake of tomato seedlings grown in low‐nutrient soils (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that application of biofertilizers can effectively reduce the use of chemical fertilizers and pesticides. Jia et al (2020) found that biofertilizers can replace 25% of chemical fertilizers without a detectable impact on the yield and quality of Chinese cabbage.…”
Section: Discussionmentioning
confidence: 99%
“…The soil pH and EC were determined using a pH meter and EC meter, respectively, in a 1:10 soil-to-water (w/v) suspension. Soil organic matter (SOM) was analyzed using the oil bath-K 2 Cr 2 O 7 titration method (Jia et al 2020). Soil alkali-hydrolyzed nitrogen (AN), AP and AK were determined by the alkali-hydrolyzed diffusion method, molybdenum blue colorimetric method and ame photometry, respectively (Song 2020; Jia et al 2020).…”
Section: Experimental Designmentioning
confidence: 99%
“…Meng et al (2018) found that relatively long and large rice root systems contributed to relatively high biomass and seed yield. Nutrient accumulation in plants and the fertility of the environment they are in have also been shown to have a direct effect on plant growth and yield improvement (Jia et al 2020;Magwaza et al 2020). The nitrate content of pakchoi had a strong positive correlation with TN, SOM and soil available nutrients, while the soluble sugars of pakchoi were negatively correlated with soil AN and AK.…”
Section: Relationships Between Soil Properties and Physiological Char...mentioning
confidence: 99%